ANALYSIS AND PREDICTION OF APPLE PRODUCTION IN THE REPUBLIC OF SERBIA AND BOSNIA AND HERZEGOVINA - Užar, Dubravka; Tekić, Dragana; Mutavdžić, Beba (Ekonomija - teorija i praksa, 2022)
The paper analyzes the parameters of apple production in the Republic of Serbia and Bosnia and Herzegovina in the period 2006-17. The prediction of apple production parameters for next year was carried out using the linear trend model and moving average. The following parameters were analyzed: harvested area (ha), yield (t/ha) and total production (t). On average, there were 24,760 hectares with apple trees in Serbia and 19.040 hectares in Bosnia and Herzegovina. The average apple yield was 12.7 t/ha in Serbia and 3.43 t/ha in Bosnia and Herzegovina. In the observed period, there was an average tendency of increase in yield by 3.78% per year in Serbia, whereas in Bosnia and Herzegovina, there was a noticeable negative rate, namely a tendency of yield decline by 1.17% on average per year. The average annual apple production in Serbia was 313,177 tons and in the analyzed period there was a tendency of increase in yield by 4,22%. In Bosnia and Herzegovina, the average annual apple production was 65,186 tons and in the analyzed period there was a negative rate of 0.96% i.e. a decline in yield. In the next year, the Republic of Serbia should achieve apple production of 431,305 tons, while Bosnia and Herzegovina is expected to produce 60,657 tons